Experiences of Discrimination and Everyday Racism Among Children and Adolescents With an Immigrant Background – Results of a Systematic Literature Review on the Impact of Discrimination on the Developmental Outcomes of Minors Worldwide - Metzner, Franka; Adedeji, Adekunle; Wichmann, Michelle L.-Y.; Zaheer, Zernila; Schneider, Lisa; Schlachzig, Laura; Richters, Julia; Heumann, Susanne; Mays, Daniel (Frontiers in Psychology, 2022)
Experiences of discrimination such as everyday racism can negatively affect the mental and physical health of children and adolescents with an immigrant background and impair their integration process in the host societies. Although experiences of racism are part of the everyday life of many minors affected by the process of “Othering” (e.g. those with an immigrant background), an overview of empirical findings is missing for this age group worldwide. A systematic review was conducted to identify and analyse international research on the impact of discrimination on the developmental outcomes and integration of immigrant children and adolescents. Three scientific databases were systematically searched up to June 11, 2021. A total of k=4,769 identified publications were reviewed based on inclusion and exclusion criteria in terms of the PICOS format by independent reviewers. Thirty-four primary studies published between 1998 and 2021 met all inclusion criteria. The samples examined were mainly migrant youth (k=30), with only k=2 studies assessing refugee youth and k=1 study assessing both migrant and refugee youth. The majority of included studies assessed perceived discrimination, with only k=1 study directly assessing experiences of racism. The association between discrimination or racism and developmental outcomes was assessed by the included studies within the three main topics of (a) mental and physical health-related outcomes (k=30, e.g. self-esteem, depressive symptoms), (b) school-related outcomes (k=6, e.g. academic achievement), and (c) other developmental outcomes (k=13, e.g. misconduct or delinquency). Data collection procedures were implemented, and findings on minors’ developmental outcomes and integration processes who experience discrimination and racism were summarised and discussed. The current review suggests experienced (racial) discrimination as a negative predictor of children and adolescents’ (mental) health-related outcomes, while no clear results could be found for the association between discrimination and school-related outcomes. A need for more empirical research focusing on the path and (possibly) indirect link between discrimination and children and adolescents’ school-related outcomes as well as resulting school recommendations and the chosen career path was derived.